A Dual-Crosslinked and Anisotropic Regenerated Cellulose/Boron Nitride Nanosheets Film With High Thermal Conductivity, Mechanical Strength, and Toughness - Xu, Xuran; Su, Yichuan; Zhang, Yongzheng; Wu, Shuaining; Wu, Kai; Fu, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
Highly thermo-conductive but electrically insulating film, with desirable mechanical performances, is extremely demanded for thermal management of portable and wearable electronics. The integration of boron nitride nanosheets (BNNS) with regenerated cellulose (RC) is a sustainable strategy to satisfy these requirements, while its practical application is still restricted by the brittle fracture and lose of toughness of the composite films especially at the high BNNS addition. Herein, a dual-crosslinked strategy accompanied with uniaxial pre-stretching treatment was introduced to engineer the artificial RC/BNNS film, in which partial chemical bonding interactions enable the effective interfiber slippage and prevent any mechanical fracture, while noncovalent hydrogen bonding interactions serve as the sacrifice bonds to dissipate the stress energy, resulting in a simultaneous high mechanical strength (103.4 MPa) and toughness (10.2 MJ/m3) at the BNNS content of 45 wt%. More importantly, attributed to the highly anisotropic configuration of BNNS, the RC/BNNS composite film also behaves an extraordinary in-plane thermal conductivity of 15.2 W/m·K. Along with additional favorable water resistance and bending tolerance, this tactfully engineered film ensures promised applications for heat dissipation in powerful electronic devices.